Opportunistic Fonsecaea pedrosoi brain abscess in a patient with non-cirrhotic portal fibrosis-induced hypersplenism- a novel association. (October 2013) - Madhugiri, Venkatesh S.; Singh, Rakesh; Vyavahare, Mukta; Vijayahari, Ranjit; Sasidharan, Gopalakrishnan M.; Kuma, V. R. Roopesh; Jacob, Sajini; Verma, Surendra K.; Ananthakrishnan, Ramesh; Yadav, Awdhesh K.; Gundamaneni, Sudheer Kumar
Abstract Non-cirrhotic portal fibrosis, a common cause of splenomegaly in tropical countries, can lead to hypersplenism and pancytopenia. Hypersplenism in this setting has not been associated with opportunistic infections. We describe a patient with hypersplenism secondary to non-cirrhotic portal fibrosis who developed a Fonsecaea pedrosoi brain abscess and succumbed to the illness despite aggressive management.